2012
DOI: 10.1186/1756-9966-31-66
|View full text |Cite
|
Sign up to set email alerts
|

Propofol induces proliferation and invasion of gallbladder cancer cells through activation of Nrf2

Abstract: BackgroundPropofol is one of the most commonly used intravenous anaesthetic agents during cancer resection surgery, but the effect of propofol on gallbladder cancer is not clear. NF-E2-related factor 2 (Nrf2) is abundantly expressed in cancer cells and relates to proliferation, invasion, and chemoresistance. The aims of the current study were to evaluate effects of propofol on the behavior of human GC cells and role of Nrf2 in these effects.MethodThe effects of propofol on cell proliferation, apoptosis, and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
2
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(75 citation statements)
references
References 22 publications
3
69
2
1
Order By: Relevance
“…Previous reports have shown that within the nucleus NRF2 signals in pro-survival pathways (Niture and Jaiswal, 2012;Ohta et al, 2008), triggers proliferation (Homma et al, 2009;Zhang et al, 2012) and is implicated in drug resistance (Wang et al, 2008). Similarly, knockdown of NRF2 has been reported to curb growth of tumour in vivo and in vitro (Manandhar et al, 2010;Singh et al, 2008).…”
Section: Cells Utilise Basal Ros To Control Nrf2 Subcellular Compartmmentioning
confidence: 93%
“…Previous reports have shown that within the nucleus NRF2 signals in pro-survival pathways (Niture and Jaiswal, 2012;Ohta et al, 2008), triggers proliferation (Homma et al, 2009;Zhang et al, 2012) and is implicated in drug resistance (Wang et al, 2008). Similarly, knockdown of NRF2 has been reported to curb growth of tumour in vivo and in vitro (Manandhar et al, 2010;Singh et al, 2008).…”
Section: Cells Utilise Basal Ros To Control Nrf2 Subcellular Compartmmentioning
confidence: 93%
“…However, increasing evidence has demonstrated that propofol has numerous non-anesthetic effects (12). In recent years, studies have confirmed the anti-cancer properties of propofol, including the repression of cell metastasis, adhesion and proliferation as well as induction of cell apoptosis (13)(14)(15). Thus, propofol has an important role in maintaining the balance of cell proliferation and apoptosis, the dysregulation of which is implicated in EM-associated processes.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al [30] studied the effect of propofol on the proliferation, apoptosis, and invasion of cholangiocarcinoma cell cultures and found that proliferation and invasion of the cancer was increased and apoptosis was decreased in a dose-dependent manner with increasing doses of propofol perhaps by up-regulating Nrf2 which is a transcription factor activated by stress.…”
Section: Intravenous Anesthetic Agents and Tivamentioning
confidence: 98%